Hub-Periphery Development Pattern and Inclusive Growth : Case Study of Guangdong Province - Luo, Xubei; Zhu, Nong (World Bank, Washington, DC, 2015)
The hub-periphery development pattern of the Guangdong economy, to some extent, is a miniature of that of the Chinese economy. The Pearl River Delta, drawing from its first-nature comparative advantages in factor endowments and proximity to Hong Kong SAR, China, and Macau SAR, China, and the second-nature advantages as first-movers in the reforms in attracting and retaining domestic and foreign resources, has developed into a regional economic center. This paper examines the pattern of inter- and intra-provincial migration and that of the concentration of production, to explore the challenges and opportunities for the success of “double transfer.” The paper suggests a four-prong approach, to improve the business environment, support the realization of latent comparative advantages, increase the skill level of the labor force to support the upgrade of the production structure, and protect the vulnerable, to support the inclusive growth of the economy in Guangdong in a sustainable manner.